THE WELDING OF SHAN-THAI - Hirsch F.; Ishida K.; Kozai T.; Meesook A. (My University, 2006)
The Shan-Thai Terrane is viewed as a remnant of paleo-Tethys in South East Asia. The more internal “Thai” elements of Shan-Thai, bordering with Indochina, are of Cathaysian type, while the more central part of the terrane is of transitional “Sibumasu” character: The external “Shan” elements of Shan-Thai that left Gondwana last have a clear cold-water imprint. Petrological and paleontological evidence corroborates the end Triassic—earliest Jurassic Late Indosinian orogeny, as the main Paleotethyan tectonic closure event. Its main axis consists of the Mae-Sariang Zone, which can be followed over Mae Sot to Kanchanaburi and Chanthaburi, from where it extends into southern Thailand and Peninsular Malaysia. Cenozoic Himalayan escape tectonics, alternating strike-slip movements and rotation severely compressed Shan-Thai, opened the Gulf of Thailand, disrupted the original alignment of the Mae Sariang zone and Gondwana-Tethys divide, and shaped the present tectonic configuration of SE Asia.
Keywords: INDOSINIAN OROGENY; PALEO-TETHYS; SHAN-THAI; MAE-SARIANG ZONE; GONDWANA-TETHYS DIVIDE; Jurassic; Triassic; Mesozoic::Jurassic; Мезозой::Юрская; Mesozoic::Triassic; Мезозой::Триасовая